which of the following recursive formulas represent the same arithmetic sequence as the explicit formula an=5+(n-1)2
a. a1=5
an=an-1+2
b. a1=5
an=(an-1+2)5
c. a1=2
an=an-1+5
d. a1=2
an=an-1*5

Respuesta :

Answer:

Choice A:

[tex]a_1=5[/tex]

[tex]a_{n}=a_{n-1}+2[/tex]

Step-by-step explanation:

[tex]a_n=5+(n-1)2[/tex]

means we looking for first term 5 and the sequence is going up by 2.

In general,

[tex]a_n=a_1+(n-1)d[/tex]

means you have first term [tex]a_1[/tex] and the sequence has a common difference of d.

So it is between the first two choices.

The explicit form of an arithmetic sequence is: [tex]a_n=a_1+(n-1)d[/tex]

An equivalent recursive form is [tex]a_n=a_{n-1}+d \text{ where } a_1 \text{ is the first term}[/tex]

So d again here is 2.

So choice a is correct.

[tex]a_1=5[/tex]

[tex]a_{n}=a_{n-1}+2[/tex]

Answer: Option a

[tex]\left \{ {{a_1=5} \atop {a_n=a_{(n-1)}+2}} \right.[/tex]

Step-by-step explanation:

The arithmetic sequences have the following explicit formula

[tex]a_n=a_1 +(n-1)*d[/tex]

Where d is the common difference between the consecutive terms and [tex]a_1[/tex] is the first term of the sequence:

The recursive formula for an arithmetic sequence is as follows

[tex]\left \{ {{a_1} \atop {a_n=a_{(n-1)}+d}} \right.[/tex]

Where d is the common difference between the consecutive terms and [tex]a_1[/tex] is the first term of the sequence:

In this case we have the explicit formula [tex]a_n=5+(n-1)*2[/tex]

Notice that in this case

[tex]a_1 = 5\\d = 2[/tex]

Then the recursive formula is:

[tex]\left \{ {{a_1=5} \atop {a_n=a_{(n-1)}+2}} \right.[/tex]

The answer is the option a.